دور القصة في تنمية الذكاء الوجداني لدى طفل الروضة من وجهة نظر المربيات - عوين, بلقاسم; الأرقط, عائشة (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة إلى التعرف على دور القصة في تنمية الذكاء الوجداني لدى طفل الروضة من وجهة نظر المربيات، ولتحقيق هذا الهدف تم استخدام المنهج الوصفي الاستكشافي وقد شملت عينة الدراسة على (20) مربية. وقد أشرنا مربيات رياض الأطفال ببلديتي الرباح والبياضة إلى أن القصة لها أهمية كبيرة في تنمية الذكاء الوجداني لأطفال الروضة، وكذلك أظهرت الدراسة النتائج التالية: - يتميز أغلبية أطفال الرياض بمستوى ذكاء وجداني مرتفع بعد السماع للقصة من وجهة نظر المربيات. - لا توجد فروق بين الذكور والإناث من أطفال الرياض في الذكاء الوجداني وأبعاده من وجهة نظر المربيات. Abstract: The study aimed to identify the role of the story in developing emotional intelligence in the kindergarten child from the point of view of the nannies. We have indicated kindergarten nannies in the municipalities of Al -Rabah and Al -Baydah that the story is of great importance in developing the emotional intelligence of kindergarten children, and the study also showed the following results: • The majority of Riyadh children are characterized by a high level of emotional intelligence after hearing the story from the point of view of the nannies. There are no differences between males and females from Riyadh children in emotional intelligence and its dimensions from the point of view of the nannies.
The role of the story in developing emotional intelligence in the kindergarten child from the point of view of the nannies
مقال
Keywords: القصة ، الذكاء الوجداني ، طفل الروضة ، مربيات; the story , Emotional intelligence , Kindergarten child , Nannies